18F‐FDG uptake in accessory respiratory muscles shows the respiratory effort of patients with pleuroparenchymal fibroelastosis. Issue 2 (20th January 2022) - Okabayashi, Hiroko; Machida, Hiroko; Masunaga, Aiko; Ichiyasu, Hidenori; Sakagami, Takuro
Abstract: Patients with pleuroparenchymal fibroelastosis (PPFE) have severe breathlessness even with mild hypoxaemia. In patients with PPFE, accessory respiratory muscles, such as the sternocleidomastoid muscles, are used to maintain ventilation. An intense 18 F‐fluorodeoxyglucose uptake in accessory respiratory muscles using positron emission tomography/computed tomography reflects the strong respiratory effort of patients with PPFE. Abstract : In patients with severe respiratory disease, accessory respiratory muscles, such as the sternocleidomastoid muscles, are used to maintain ventilation. We present a patient with pleuroparenchymal fibroelastosis with intense 18 F‐fluorodeoxyglucose uptake in accessory respiratory muscles using positron emission tomography/computed tomography reflecting the strong respiratory effort.